2016
DOI: 10.5902/2316980x21143
|View full text |Cite
|
Sign up to set email alerts
|

Densidade de Fluxo de Fótons (DFF) em um sistema de Integração Lavoura-Pecuária-Floresta (ILPF)

Abstract: Resumo: Este estudo foi realizado em um sistema de produção integrado lavoura-pecuária-floresta no município de Cachoeira Dourada, Goiás, Brasil. A pesquisa colabora para um melhor entendimento da interação planta-ambiente, esta foi realizada com o objetivo de analisar a entrada de luz em dois períodos diferentes (estação seca e chuvosa). Para a coleta da Densidade de Fluxo de Fótons (DFF) (µmol.m-2 .s-1 ) foi utilizado dois sensores de quanta LI-250 A, Li-cor Inc., USA, na faixa fotossinteticamente ativa. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…According to these authors, variations in nutrient content in different litter compartments can be observed in the same species, given site and plants' features, and features of the element itself. Based on Leite et al (2011), variations in the same element can happen within the same forest species, although Guimarães;Calil (2017) stated that nutrient concentration in each compartment is related to its function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to these authors, variations in nutrient content in different litter compartments can be observed in the same species, given site and plants' features, and features of the element itself. Based on Leite et al (2011), variations in the same element can happen within the same forest species, although Guimarães;Calil (2017) stated that nutrient concentration in each compartment is related to its function.…”
Section: Discussionmentioning
confidence: 99%
“…Production cost reduction and income diversification are among the benefits from this system (ALVARENGA et al, 2010), as well as water, soil and climate resource conservation, recovery of degraded areas, natural pest and disease control, greenhouse gas emission reduction (BALBINO et al, 2011), changes in microclimate such as temperature and humidity (GUIMARÃES;CALIL, 2017), light, wind, pH andC andN stock (BENAVIDES et al, 2009), and soil quality changes naturally motivated by nutrient cycling due to treecomponent presence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is near and washed by the waters of the Paranaíba River and the Rio Meia Ponte (GUIMARÃES et al, 2016).…”
Section: Characterization Of the Study Areamentioning
confidence: 99%
“…with regards to the different litter compartment: leaves, branches, bark and wood (GUIMARÃES et al, 2016).…”
Section: Analysis Of the Main Components Of Nutritional Contentsmentioning
confidence: 99%